Mothers with a history of trauma and their children: a systematic review of treatment interventions - van Ee, Elisa; Meuleman, Eline M. (Frontiers in Psychology, 2024)
Introduction -Mothers with a history of trauma frequently face significant challenges in their relationships with their children. Therefore, it is crucial for trauma-exposed mothers and their young children to receive adequate trauma-informed treatment. This review aimed to examine the effects of trauma-informed interventions on improving the mother-child relationship among mothers with a history of trauma and their young children under six years old.Methods -The study analyzed fifteen articles that met the eligibility criteria, encompassing a sample size of 1,321 mothers. The systematic GRADE approach was used to rate the certainty of evidence in this systematic review.-The study found that while some interventions demonstrated small to large effects, the quality of evidence was only moderate. The most promising interventions were Parent-Child Interaction Therapy (PCIT), Child-Parent Psychotherapy (CPP), and Maternal Empowerment Program (MEP), which all included elements of psychotherapy, psychoeducation, and skills training. Discussion -The study underscores the importance of understanding the needs of motherchild dyads affected by trauma and tailoring interventions to meet those needs. Overall, the literature suggests that interventions combining psychotherapeutic, psychoeducational, and skills-training components are most effective in improving mother and child-related outcomes for mothers with a history of trauma and their young children. The review provides recommendations for future research and emphasizes the importance of considering the mother-child relationship in trauma-informed interventions.